Problematika Kebijakan Hukum Terbuka (Open Legal Policy) Masa Jabatan Hakim Konstitusi - Athari Farhani; Ibnu Sina Chandranegara (Jurnal Konstitusi, 2020)
Discourse about periodization of the term of office of the Constitutional Court judge ended at the Constitutional Court Decision Number 53/PUU-XIV/2016 and Number 73/PUU-XIV/2016 which transferred the authority of regulating the term of the constitutional judge to be fully regulated by the legislators (open legal polic). This article discusses the problem of the term of office of the Constitutional Court judge, if it is regulated as an open legal policy for the quality of the independence of judicial power held by the Constitutional Court. This article was prepared based on the results of normative legal research using the statutory approach. This article provides two conclusions. First, the open legal policy in determining the periodization of the term of constitutional judge has the potential to reduce the degree of independence of the judicial power. Second, a relatively long period of time is an ideal concept for the term of office of constitutional judge. The term of office of constitutional judge should be aligned with the Supreme Court’s tenure.